ANALISIS EVENT STUDY NEW NORMAL TERHADAP HARGA SAHAM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Leni Leni; Harti Budi Yanti (STMIK Widuri Jakarta, 2023)
This study aims to analyze abnormal returns and trading volume activity before and after the announcement of the implementation of the new normal in the goods and consumption sector. The object of research is through the official website of the Indonesia Stock Exchange (IDX). Retrieval of data using the documentation method, collecting data and information from www.idx.co.id and the website www.finance.yahoo.com which contains daily stock prices covering the number of stock trading transactions and the total number of shares outstanding at the time of observation. The results of the first hypothesis study show that there is no difference in abnormal returns before and after the announcement of the implementation of the new normal in goods and consumption sector companies. The second hypothesis shows that there is no difference in trading volume activity before and after the announcement of the implementation of the new normal in goods and consumption sector companies. This shows that the stock market does not react around the announcement of the implementation of the new normal. Investors do not react to buying or selling shares on the Indonesia Stock Exchange (IDX)